1960
DOI: 10.1192/bjp.106.445.1230
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Structure in Thought-Disordered Schizophrenics

Abstract: “Thought-disorder” in schizophrenia was initially a psychiatric concept derived from clinical observation. As crystallized in standard psychiatric authorities, say Mayer-Gross, Slater and Roth (1954) the primary features of the talk (and inferentially the thinking) of thought-disordered schizophrenic patients are: (i)Inconsequential following of side issues.(ii)Tendencies for the thought to be directed by alliterations, analogies, clang associations, associations with accidents of the speaker's environment, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
4

Year Published

1965
1965
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(82 citation statements)
references
References 11 publications
0
78
0
4
Order By: Relevance
“…El índice de intensidad de Bannister (1960), tomado constructo a constructo nos indica la centralidad de ese constructo. Se computa elevando al cuadrado la correlación de un constructo con cada uno de los demás, promediando estos resultados y extrayendo su raíz cuadrada.…”
Section: C) Centralidad De Los Constructosunclassified
“…El índice de intensidad de Bannister (1960), tomado constructo a constructo nos indica la centralidad de ese constructo. Se computa elevando al cuadrado la correlación de un constructo con cada uno de los demás, promediando estos resultados y extrayendo su raíz cuadrada.…”
Section: C) Centralidad De Los Constructosunclassified
“…A form of the repertory grid technique of Kelly [2,6], modified by Bannister [1] was used. It already proved to be a valid method for such purposes [3]'.…”
Section: Methodsmentioning
confidence: 99%
“…This was 1 1 The description of the method for such purposes, attempts to validate it and other applications of it are described by Crisp [31.…”
Section: First Groupmentioning
confidence: 99%
“…Bannister (1960Bannister ( , 1962 gave a group of constructs to a normative group and a mean relationship for each pair of constructs was derived. A single subject's grid could be compared to these normative relationships to obtain a measure of social deviation.…”
Section: The_se£testmentioning
confidence: 99%
“…Bannister (1960) In a retest of the hypothesis (Bannister, 1965), he found that validation led to increased relationships between constructs, but invalidation produced no change, as if subjects were resisting a change that would leave them with no alternative system. However, if, of two constellations of constructs, one was validated and the other constellation repeatedly invalidated, then the appropriate increase or de crease in the relationships of constructs within the constellation occurred.…”
Section: Schiz2ehrenia_an^personal_çoeistruçtsmentioning
confidence: 99%